Pre-Film Formation and Cycle Performance of Silicon-Flake-Powder Negative Electrode in a Solvate Ionic Liquid for Silicon-Sulfur Rechargeable Batteries. Issue 9 (1st January 2018) - Haruta, Masakazu; Moriyasu, Takashi; Tomita, Akira; Takenaka, Toshio; Doi, Takayuki; Inaba, Minoru
Abstract : In developing silicon-sulfur batteries with a high energy density, the cycle performance of a Si-flake-powder (Si LeafPowder, Si-LP) negative electrode in a solvate ionic liquid of lithium salt-glyme equimolar complex electrolyte were improved by stable pre-film formation on the Si-LP. The pre-film was formed by pre-cycling in a fluoroethylene carbonate-based electrolyte prior to cycle tests in the glyme-based electrolyte. The capacity retention of the pre-cycled Si-LP electrode in the glyme-based electrolyte improved remarkably. Surface deposition originating from decomposition products of the electrolyte decreased by formation of the pre-film. The pre-film consisted of fine LiF grains and organo-fluorine compounds, the combination of which is important for inhibiting decomposition of the glyme-based electrolyte on Si negative electrodes.